(3GdCeQ GdLfGFi (B/ s - (3CTQa eSYO CHhRjO s; (3WGQb SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3GdCeQ GdLfGFi jYO ef Cge GdhSGFd dYdGL CReI GdYOGdI GdLfGFjI hgh jYO CeQG bVGFjG HJhbjY GdYbhHI GdebQQI HOhf JMbjb Ch eQGaYI (B. (3hPdc jYfi Cf GdCeQ GdLfGFi jUOQ Ohf GJHGY GdbhGYO GdNGUI HELQGAGJ GdeMGceI hGdJMbjb GdfgGFi GddGRe ddMce GdLfGFi (B. (3aGdCeQ GdLfGFi CeQ jUOQ ef bGVi GdeMceI GdLRFjI Ch ef cd YVh fjGHI ef OQLI hcjd fjGHI Ydi GdCbd HGdeMceI GdJi ef GNJUGUgG fXQ GdOYhI HJhbjY YbhHI LfGFjI ai GdLfM hGdeNGdaGJ GdLGFR ajgG Pdc bGfhfG hPdc HYO GdGWdGY Ydi GdChQGb ai ZjQ MVhQ GdNUhe hHZjQ ELQGA JMbjb Ch SeGY eQGaYIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B505-535s
Keywords: (3HOGFd GdOYhi GdLfGFjIs; (3GdGLQGAGJ GdLfGFjI GdehLRI s; (3GdGhGeQ GdLfGFjIs; (3GdfjGHI GdYGeIs; (3GdfXGe GdGJgGeis; (3GdbhGfjf GdGLfHjIs; (3GdfXGe GdGLQGFi GdeUQis; (3hdGjJi GdMSHI hGdTQWs; (3GdYed GdbVGFis; (3GdGYeGd GdhdGFjIs; (3GdHWdGfs; (3GdGTcGd ai JfajP GdGeQ GdLfGFis; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs